PET (Polyethylene Terephthalate) adhesive film as well as preparation method and application thereof
By setting up a multi-layer coating on the PET film, using the resin and nanodispersed slurry in the laser engraving coating, the laser engraving function of the PET tape film at a wavelength of 1064nm is realized, which solves the problem of PET materials lacking laser engraving performance, and maintains good heat resistance and bending resistance.
Patent Information
- Application Number
- CN202510081645.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
PET materials lack laser engraving function in the 1064nm band, which cannot replace the application of traditional PVC materials in bank card protection films, although PET materials have better heat resistance and bending resistance.
By laminating the polyurethane adhesive coating, adhesion promotion coating and laser engraving coating on the PET film, the resin coating liquid and nanodispersed slurry in the laser engraving coating are used to realize the 1064nm wavelength laser engraving function of the PET tape film.
The PET tape film not only has laser engraving function, but also maintains excellent heat resistance and bending resistance. It has a more stable structure when applied to bank cards, a clear laser engraving effect and is not easy to bubble.
Smart Images

Figure CN119899595A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite films, and in particular to a PET adhesive film and a preparation method and application thereof. Background Art
[0002] At present, bank card protective films with laser engraving function are almost all made of PVC material, and PET material does not have the laser engraving function under the 1064nm band. However, PET material has better heat resistance and bending resistance than PVC material, so how to make PET material have laser engraving performance is the problem that the patent of this invention needs to solve. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a PET adhesive film and a preparation method and application thereof. The PET adhesive film provided by the present invention has not only a laser engraving function, but also excellent heat resistance and bending resistance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a PET adhesive film, comprising a polyurethane adhesive coating, a PET film, an adhesion promoting coating and a laser engraving coating which are stacked;
[0006] The laser engraving coating is prepared from a laser engraving coating, and the laser engraving coating comprises a resin coating liquid and a nano-dispersed slurry;
[0007] The resin coating liquid includes vinyl chloride-vinyl acetate resin, polyurethane resin and organic ketone;
[0008] The nano-dispersed slurry comprises a laser engraving aid, a dispersing aid and an organic ketone; the laser engraving aid comprises one or more of carbon black and metal oxides.
[0009] Preferably, the metal oxide includes one or more of antimony tin oxide, neodymium oxide and zinc oxide.
[0010] Preferably, the resin coating liquid comprises the following components in weight percentage: 10-20% of vinyl chloride-vinyl acetate resin, 1-10% of polyurethane resin, and the balance is organic ketone.
[0011] Preferably, the nano-dispersed slurry comprises the following components in weight percentage: 20-40% of a laser engraving aid, 1-2% of a dispersing aid, and the balance being organic ketone.
[0012] Preferably, the dispersing aid is a phosphate dispersant or a polyurethane dispersant.
[0013] Preferably, the mass ratio of the resin coating liquid to the nano-dispersed slurry is 25:1-2.
[0014] Preferably, the adhesion-promoting coating is prepared from an aqueous acrylic coating liquid, which comprises the following components in weight percentage: 10-30% acrylic resin, 1-10% isopropyl alcohol, and the balance is water.
[0015] Preferably, the thickness of the polyurethane adhesive coating is 5 to 10 μm, the thickness of the PET film is 40 to 200 μm, the thickness of the adhesion-promoting coating is 0.1 to 2 μm, and the thickness of the laser engraving coating is 2 to 10 μm.
[0016] The present invention also provides a method for preparing the PET adhesive film described in the above technical solution, comprising the following steps:
[0017] An adhesion-promoting coating was prepared on one side of the PET film;
[0018] Applying a laser engraving coating on the surface of the adhesion promoting coating, and drying the coating to form a laser engraving coating;
[0019] A polyurethane adhesive coating is prepared on the other side of the PET film to obtain the PET adhesive film.
[0020] The present invention also provides the use of the PET adhesive film described in the above technical solution or the PET adhesive film prepared by the preparation method described in the above technical solution in bank cards.
[0021] The invention provides a PET adhesive film.
[0022] The PET adhesive film provided by the present invention uses a PET film as a substrate, and an adhesion-promoting coating and a laser engraving coating are sequentially stacked on the surface thereof. By setting the laser engraving coating of the raw material for preparing the laser engraving coating, the PET adhesive film has a laser engraving function of a wavelength of 1064nm, and can realize clear engraving of Chinese characters, numbers, letters and portraits on the surface of the PET adhesive film. At the same time, the adhesive film of the present invention uses PET as a substrate and has better heat resistance and bending resistance. In addition, the setting of the adhesion-promoting coating between the PET film and the laser engraving coating can improve the adhesion of the laser engraving coating, so that when the PET adhesive film is applied to a bank card, the structure is more stable and not easy to bubble. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A schematic diagram of the structure of the PET adhesive film provided by the present invention;
[0024] Figure 2 This is a laser engraving effect diagram of a finished card prepared using the PET adhesive film obtained in Example 1;
[0025] Figure 3This is a laser engraving effect diagram of a finished card prepared using the PET tape film obtained in Comparative Example 4;
[0026] Figure 4 This is a laser engraving effect diagram of a finished card prepared using the PVC film in Comparative Example 3;
[0027] The accompanying drawings are marked as follows: 1-laser engraving coating, 2-adhesion promoting coating, 3-PET film, 4-polyurethane adhesive coating. DETAILED DESCRIPTION
[0028] Figure 1 The schematic diagram of the PET tape film structure provided by the present invention is shown below in combination with Figure 1 The PET adhesive film provided by the present invention is described in detail.
[0029] The present invention provides a PET adhesive film, comprising a polyurethane adhesive coating, a PET film, an adhesion promoting coating and a laser engraving coating which are stacked;
[0030] The laser engraving coating is prepared from a laser engraving coating, and the laser engraving coating comprises a resin coating liquid and a nano-dispersed slurry;
[0031] The resin coating liquid includes vinyl chloride-vinyl acetate resin, polyurethane resin and organic ketone;
[0032] The nano-dispersed slurry comprises a laser engraving aid, a dispersing aid and an organic ketone; the laser engraving aid comprises one or more of carbon black and metal oxides.
[0033] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0034] The PET adhesive film provided by the present invention comprises a PET film, wherein the thickness of the PET film is preferably 40 to 200 μm, and specifically can be 40 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm or 200 μm. The present invention uses the PET film as a substrate, and has excellent heat resistance and bending resistance compared to the PVC film.
[0035] The PET adhesive film provided by the present invention includes a polyurethane adhesive coating layered on one side of the PET film, the polyurethane adhesive coating is preferably prepared from a polyurethane adhesive, the polyurethane adhesive is preferably a polyurethane water-based adhesive, and the model of the polyurethane water-based adhesive is preferably B1608, B1605 or B1601 independently developed by Tianjin Boyuan Company. In the present invention, the thickness of the polyurethane adhesive coating is preferably 5 to 10 μm, specifically 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. In the present invention, the polyurethane adhesive coating can adhere the PET adhesive film to the surface of a bank card.
[0036] The PET adhesive film provided by the present invention includes an adhesion-promoting coating layered on the other side of the PET film. In the present invention, the thickness of the adhesion-promoting coating layer is preferably 0.1 to 2 μm, specifically 0.1 μm, 0.5 μm, 1 μm, 1.5 μm or 2 μm. In the present invention, the adhesion-promoting coating layer is preferably prepared from an aqueous acrylic coating liquid. In the present invention, the aqueous acrylic coating liquid preferably includes the following components in weight percentage: 10 to 30% acrylic resin, 1 to 10% isopropanol, and the remainder is water. In the present invention, in the aqueous acrylic coating liquid, the weight percentage of acrylic resin is further preferably 15 to 25%, specifically 10%, 15%, 20%, 25% or 30%. In the present invention, in the aqueous acrylic coating liquid, the weight percentage of isopropanol is further preferably 4 to 6%, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. In the present invention, the water is preferably deionized water. In the present invention, the method for preparing the aqueous acrylic coating liquid preferably comprises the following steps: mixing acrylic resin, isopropanol and water, dissolving (referred to as the first dissolution) to obtain the aqueous acrylic coating liquid; the temperature of the first dissolution is preferably 70 to 80°C, and the time is preferably 1 to 1.5 hours; the first dissolution is preferably carried out under stirring. In the present invention, the provision of the adhesion-promoting coating can enhance the bonding force between the laser engraving coating and the PET film, so that when the PET adhesive film is applied to a bank card, the structure is more stable and it is not easy to bubble during laser engraving.
[0037] The PET adhesive film provided by the present invention includes a laser engraving coating layered on the surface of the adhesion-promoting coating. In the present invention, the thickness of the laser engraving coating is preferably 2 to 10 μm, specifically 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm. In the present invention, the laser engraving coating is prepared from a laser engraving coating, and the laser engraving coating includes a resin coating liquid and a nano-dispersed slurry; the mass ratio of the resin coating liquid to the nano-dispersed slurry is preferably 25:1 to 2, specifically 25:1, 25:1.5 or 25:2.
[0038] In the present invention, the resin coating liquid includes vinyl chloride-vinyl acetate resin, polyurethane resin and organic ketone. In the present invention, the resin coating liquid preferably includes the following components in weight percentage: 10-20% of vinyl chloride-vinyl acetate resin, 1-10% of polyurethane resin, and the balance is organic ketone. In the present invention, in the resin coating liquid, the weight percentage of vinyl chloride-vinyl acetate resin is further preferably 12-18%, specifically 10%, 12%, 14%, 15%, 16%, 18% or 20%. In the present invention, in the resin coating liquid, the weight percentage of polyurethane resin is further preferably 2-8%, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. In the present invention, the organic ketone is preferably one or more of acetone, butanone and cyclohexanone, and cyclohexanone is further preferably used. In the present invention, the method for preparing the resin coating liquid preferably comprises the following steps: mixing vinyl chloride-vinyl acetate resin, polyurethane resin and organic ketone, dissolving (referred to as the second dissolution) to obtain the resin coating liquid; the temperature of the second dissolution is preferably 60-70°C, the time is preferably 1-1.5 hours, and the second dissolution is preferably carried out under stirring. In the present invention, the resin coating liquid can realize the laser engraving function by coating on the surface of the PET film.
[0039] In the present invention, the nano-dispersed slurry includes a laser engraving aid, a dispersing aid and an organic ketone. In the present invention, the nano-dispersed slurry preferably includes the following components in weight percentage: 20-40% laser engraving aid, 1-2% dispersing aid, and the balance is organic ketone. In the present invention, in the nano-dispersed slurry, the weight percentage of the laser engraving aid is further preferably 25-35%, specifically 20%, 25%, 30%, 35% or 40%, and the laser engraving aid includes one or more of carbon black and metal oxides; the metal oxide preferably includes one or more of antimony tin oxide, neodymium oxide and zinc oxide. In the present invention, in the nano-dispersed slurry, the weight percentage of the dispersing aid is further preferably 1.2-1.8%, specifically 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%; the dispersing aid is preferably a phosphate dispersant or a polyurethane dispersant; the model of the phosphate dispersant is preferably DAP-10 (purchased from Guangzhou Si Tuyuan Company) or Evonik 655 (purchased from Beijing Kemite Company); the model of the polyurethane dispersant is preferably SY-1663 (purchased from Jiangxi Mitsukoshi Company). In the present invention, the type of the organic ketone is preferably consistent with the above technical solution, which will not be repeated here. In the present invention, the preparation method of the nano-dispersed slurry preferably includes the following steps: mixing a laser engraving aid, a dispersing aid and an organic ketone, and grinding to obtain the nano-dispersed slurry; the grinding time is preferably 2-3 hours, and the grinding is preferably carried out in a grinder. In the present invention, the particle size D of the nano-dispersed slurry 50 Preferably less than 500 nm.
[0040] The present invention sets the laser engraving coating so that the PET tape film has a laser engraving function of a wavelength of 1064nm, especially the laser engraving aid in the laser engraving coating. The laser beam of a specific wavelength of the laser generator is irradiated to the surface of the PET tape film. The laser engraving aid in the PET tape film absorbs the energy of the laser. When the laser energy is absorbed, the local temperature of the PET tape film rises rapidly, causing the PET tape film to melt and vaporize. As the temperature rises sharply, after reaching the melting point of each material in the PET tape film, the PET tape film begins to melt. If the laser energy continues to act, the temperature further rises to the boiling point, and the PET tape film will vaporize. The laser beam moves according to a pre-set pattern or text path, and the PET tape film where it passes will continuously melt and vaporize, thereby removing this part of the PET tape film, forming the shapes of pits, lines, etc. required for engraving, and achieving the engraving effect. In addition, after absorbing laser energy, the PET adhesive film of the present invention will also undergo a thermal decomposition reaction, resulting in the escape of some small molecular substances, while leaving a carbonized part, which can also highlight the engraved pattern or text. After thermal decomposition and carbonization under the action of laser, it will present a color different from the original plastic, making the engraved content clearer, which is the key to realizing the laser engraving function.
[0041] The present invention also provides a method for preparing the PET adhesive film described in the above technical solution, comprising the following steps:
[0042] An adhesion-promoting coating was prepared on one side of the PET film;
[0043] Applying a laser engraving coating on the surface of the adhesion promoting coating, and drying the coating to form a laser engraving coating;
[0044] A polyurethane adhesive coating is prepared on the other side of the PET film to obtain the PET adhesive film.
[0045] The present invention prepares an adhesion-promoting coating on one side of the PET film.
[0046] In the present invention, the preparation of the adhesion-promoting coating preferably comprises the following steps: coating a water-based acrylic coating liquid on one side of the PET film and drying. In the present invention, the drying is preferably performed in an oven.
[0047] After the adhesion promoting coating is prepared, the present invention applies a laser engraving coating on the surface of the adhesion promoting coating, and forms a laser engraving coating after drying.
[0048] In the present invention, the drying is preferably performed in an oven.
[0049] After forming the laser engraving coating, the present invention prepares a polyurethane adhesive coating on the other side of the PET film to obtain the PET adhesive film.
[0050] In the present invention, the preparation of the polyurethane adhesive coating preferably includes the following steps: coating the polyurethane adhesive on the other side of the PET film and drying it.
[0051] In the present invention, the drying is preferably performed in an oven.
[0052] The present invention also provides the use of the PET adhesive film described in the above technical solution or the PET adhesive film prepared by the preparation method described in the above technical solution in bank cards.
[0053] In the present invention, when the PET adhesive film is applied to a bank card, the polyurethane adhesive coating in the PET adhesive film contacts the surface of the bank card.
[0054] In the present invention, when the PET adhesive film is applied to a bank card, it is preferably laminated together by heat pressing.
[0055] The PET adhesive film provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0056] Example 1
[0057] A method for preparing a PET adhesive film comprises the following steps:
[0058] The preparation steps of the aqueous acrylic coating liquid are as follows: 20wt% of acrylic resin, 8wt% of isopropanol and the balance of deionized water are added into a reactor, the temperature is raised to 75±5°C, and stirring is continued for 1.5h until the materials are completely dissolved, thereby obtaining the aqueous acrylic coating liquid.
[0059] The preparation steps of the resin coating liquid are as follows: 20wt% of vinyl chloride-vinyl acetate resin, 5wt% of polyurethane resin, and the balance of cyclohexanone are added into a reactor, the temperature is raised to 65±5°C, and stirring is continued for 1.5h until the materials are completely dissolved to obtain the resin coating liquid.
[0060] The preparation steps of the nano-dispersed slurry are as follows: 20 wt% of laser engraving aid (specifically antimony tin oxide), 1 wt% of dispersing aid (specifically DAP-10), and the balance of cyclohexanone are added to a grinder for grinding and dispersion, and the grinding is continued for 2 hours until the particle size D 50 Less than 500nm, a nano-dispersed slurry is obtained.
[0061] The preparation steps of the laser engraving coating are as follows: the resin coating liquid and the nano-dispersed slurry are uniformly mixed in a mass ratio of 25:2 to obtain the laser engraving coating.
[0062] The aqueous acrylic coating liquid was applied to one side of a PET film (thickness: 40 μm), and the coating was dried in a drying oven to form an adhesion-promoting coating with a thickness of 0.5 μm.
[0063] A laser engraving coating is coated on the surface of the adhesion promoting coating and dried in a drying oven to form a laser engraving coating with a thickness of 10 μm.
[0064] A polyurethane water-based adhesive (model B1601) was coated on the other side of the PET film and dried to form a polyurethane adhesive coating with a thickness of 8 μm, thereby obtaining a PET adhesive film.
[0065] Example 2
[0066] The difference from Example 1 is that in the nano-dispersed slurry, the laser engraving auxiliary agent is the metal oxide zinc oxide, and the rest is the same as Example 1.
[0067] Example 3
[0068] The difference from Example 1 is that in the nano-dispersed slurry, the laser engraving auxiliary agent is carbon black, and the rest is the same as Example 1.
[0069] Example 4
[0070] The difference from Example 1 is that the resin coating liquid and the nano-dispersed slurry are evenly mixed in a mass ratio of 25:1.5 to obtain a laser engraving coating.
[0071] Example 5
[0072] The difference from Example 1 is that the resin coating liquid and the nano-dispersed slurry are evenly mixed in a mass ratio of 25:1.0 to obtain a laser engraving coating.
[0073] Comparative Example 1
[0074] The difference from Example 1 is that the vinyl chloride-vinyl acetate resin in the resin coating liquid is omitted, and the rest is the same as Example 1.
[0075] Comparative Example 2
[0076] The difference from Example 1 is that the polyurethane resin in the resin coating liquid is omitted, and the rest is the same as Example 1.
[0077] Comparative Example 3
[0078] The difference from Example 1 is that the PET adhesive film is entirely replaced by a PVC film with a thickness of 40 μm.
[0079] Comparative Example 4
[0080] The difference from Example 1 is that no laser engraving auxiliary agent is added to the nano-dispersed slurry.
[0081] The adhesive films obtained in Example 1 and Comparative Example 4 and the PVC film in Comparative Example 3 were adhered to the surface of a bank card and laser engraved. The laser wavelength of the laser engraving was set to 1064 nm. The surface photo of the obtained bank card is as shown in FIG. Figure 2 to Figure 4 As shown, Figure 2 This is a laser engraving effect diagram of a finished card prepared using the PET adhesive film obtained in Example 1. Figure 3 This is a laser engraving effect diagram of a finished card prepared using the PET tape film obtained in Comparative Example 4. Figure 4 This is a laser engraving effect diagram of a finished card made from the PVC film in Comparative Example 3. Figure 2 It can be seen that the bank card with the PET film of Example 1 can also be laser engraved, and the laser engraved font is clear, which is equivalent to the effect of the bank card with the PVC film of Comparative Example 3 ( Figure 4 As shown); while the bank card attached with the film of Comparative Example 4 was laser engraved, the engraved font was unclear ( Figure 3 shown).
[0082] The adhesive films obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were adhered to the surface of a bank card. The bank cards adhered with the adhesive films were subjected to heat resistance tests and bending resistance tests using ISO / 7810 and ISO / 10373, respectively. The results are shown in Table 1.
[0083] Table 1 Performance test results
[0084]
[0085]
[0086] It can be seen from Table 1 that Examples 1 to 5 and Comparative Examples 1, 2, and 4 have better bending resistance and heat resistance than Comparative Example 3.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A PET adhesive film, characterized in that: It includes a polyurethane adhesive coating, a PET film, an adhesion promoting coating and a laser engraving coating arranged in layers; The laser engraving coating is prepared from a laser engraving coating, and the laser engraving coating comprises a resin coating liquid and a nano-dispersed slurry; The resin coating liquid includes vinyl chloride-vinyl acetate resin, polyurethane resin and organic ketone; The nano-dispersed slurry comprises a laser engraving aid, a dispersing aid and an organic ketone; the laser engraving aid comprises one or more of carbon black and metal oxides.
2. The PET adhesive film according to claim 1, characterized in that: The metal oxide includes one or more of antimony tin oxide, neodymium oxide and zinc oxide.
3. The PET adhesive film according to claim 1, characterized in that: The resin coating liquid comprises the following components in weight percentage: 10-20% of vinyl chloride-vinyl acetate resin, 1-10% of polyurethane resin, and the balance is organic ketone.
4. The PET adhesive film according to claim 1, characterized in that: The nano-dispersed slurry comprises the following components in weight percentage: 20-40% of a laser engraving auxiliary agent, 1-2% of a dispersing auxiliary agent, and the balance being organic ketone.
5. The PET adhesive film according to claim 1 or 4, characterized in that: The dispersing aid is a phosphate dispersant or a polyurethane dispersant.
6. The PET adhesive film according to claim 1, 3 or 4, characterized in that: The mass ratio of the resin coating liquid to the nano-dispersed slurry is 25:1-2.
7. The PET adhesive film according to claim 1, characterized in that: The adhesion promoting coating is prepared from an aqueous acrylic coating liquid, which comprises the following components in weight percentage: 10-30% acrylic resin, 1-10% isopropanol, and the balance is water.
8. The PET adhesive film according to claim 1, characterized in that: The thickness of the polyurethane adhesive coating is 5 to 10 μm, the thickness of the PET film is 40 to 200 μm, the thickness of the adhesion promoting coating is 0.1 to 2 μm, and the thickness of the laser engraving coating is 2 to 10 μm.
9. The method for preparing the PET adhesive film according to any one of claims 1 to 8, characterized in that: The following steps are involved: An adhesion-promoting coating was prepared on one side of the PET film; Applying a laser engraving coating on the surface of the adhesion promoting coating, and drying the coating to form a laser engraving coating; A polyurethane adhesive coating is prepared on the other side of the PET film to obtain the PET adhesive film.
10. Use of the PET adhesive film according to any one of claims 1 to 8 or the PET adhesive film prepared by the preparation method according to claim 9 in bank cards.